American delirium - González, Betina, 1972- (Henry Holt and Company, 2021)
In a small Midwestern city, the deer population starts attacking people. Beryl, a feisty senior and ex-hippie, trains a squad of fellow retirees to hunt the animals down. At the same time, a group of protesters decides to live in the woods, leaving behind the demands of modern life, including their children. Nine-year-old Berenice's mother has been gone for several days, leaving only a few clues about her past for Berenice to piece together. Vik, a taxidermist at the natural history museum and an immigrant from the Caribbean, is beginning to see the connections among the dropouts, the deer and the discord. When he finds a woman living in his closet, he is forced to get involved. As their lives start to spin out of control, they rescue one another in surprising ways.